ChemInform Abstract: Cyclopropanation Using Flow‐Generated Diazo Compounds. Issue 27 (18th June 2015) - Roda, Nuria M.; Tran, Duc N.; Battilocchio, Claudio; Labes, Ricardo; Ingham, Richard J.; Hawkins, Joel M.; Ley, Steven V.
Abstract A method for the cyclopropanation of electron‐poor olefins using unstabilized diazo compounds generated under continuous flow conditions and room temperature is developed.